Modified atmosphere packaging as a method to extend postharvest life of tulip flowers. Issue 3 (3rd July 2017) - Aros, Danilo; Orellana, Karina; Escalona, Víctor
ABSTRACT: Tulip is one of the most important cut flowers in the world market and abscission of the tepals is this species' most common symptom during vase life. To prevent these symptoms and extend postharvest life, passive and active modified atmosphere packaging (MAP) was applied at 0°C. Respiratory rate (CO2 Kg −1 h −1 ), ethylene production (µL kg −1 h −1 ) and concentration of CO2 and O2 (%) inside the packaging were evaluated during storage, while fresh weight loss (FWL) (%) and vase life (days) were assessed. Flowers stored using MAP performed significantly better than conventional packaging. A lower FWL (only up to 0.3%) was observed on MAP while FWL was as high as 18 to 21% for conventional packaging after 20 and 31 days, respectively. Vase life was 5.7 and 6.0 days for active and passive MAP, respectively compared to 3.3 days for conventional packing. Thus, MAP successfully extended postharvest life of tulip flowers.